Dejavniki proizvodnje in rabe lesa za kurjavo v Sloveniji - Leban, Vasja (Gozdarski vestnik, 2016)
Energy wood forms an important segment of renewable energy sources in Slovenia. Supply and demand for energy wood have increased drastically in the last decade. Many synergies and conflicts have been created which also shape the current energy wood production and use. This article aims at exploring and explaining the perceived driving factors of energy wood production and use in Slovenia. Qualitative research has been employed in order to explore and explain driving factors. We conducted 26 semi-structured interviews with forest-related stakeholders and performed content analyses of the transcribed interviews according to the principles of analytical hierarchy. The majority of interviewees perceive the market as the most important driving factor of energy wood production and use. According to the interviewees, the government is the key actor, able to achieve expedient implementation of preordain policies and actualize the set objectives by combining policy instruments and considering the market dynamics. Nevertheless, Slovenian decision makers together with other stakeholders will have to clearly define the strategic path we are going to follow in the near future and to specify the priority social areas where the majority of resources will be invested.
Keywords: kvalitativna raziskava; les za kurjavo; Slovenia; Slovenija